BEHAVIOR OF PINDOS LIMESTONE DURING HIGH SLOPE EXCAVATION. AN APPROACH TO INTERPRETE AND SIMULATE THE BEHAVIOR OF THE FORMATION USING SLOPE STABILTY ANALYSIS METHODS - Σφέικος A.; Στιμάρατζης Θ.; Κίλιας A.; Χρηστάρας Β. (Bulletin of the Geological Society of Greece, 2004)
The Acheloos river diversion project includes also works which improve the condition of the infrastructure network in the area. One of them was the improvement of a section at the Mouzaki - Arta national road. The road is developed through geological formations of the Pindos Zone. In the Argithea area, Karditsa County, it cuts through Cretaceous limestone bearing Calpionella. This formation develops high and steep slopes, over 50 m high. It consists of thin to medium bedded limestone, showing locally chert intercalations, and gradational transition to siliceous limestone. Thin silt or clay layers separate bedding. The formations is strongly folded and intensively jointed. The initial design proposed the construction of a slope with H:V relationship of 1:4 and benches every 20 m. The designed geometry was during and soon after excavation destroyed, due to sliding of rock particles. A new geometry was developed possessing a more stable state of dynamic equilibrium. Our task is to investigate and simulate the behavior of this formation. Based on data from both laboratory analysis and literature we ascribed the limestone formation values for its geotechnical properties. Using these values we estimate the values for the Safety Factor for the geometrical features of the slope. We control the stability of the slope using both rock mechanics and soil mechanic methods. The results point that rock formations, like the Cretaceous limestone which exhibit variation in their composition, and high contrast between the geotechnical characteristics values of the composing elements, may be considered as a material with soil properties. The Safety Factor calculation using these assumptions for the above mentioned slope, resulted a geometry close to the one developed. Therefore we conclude that such rock material and formations may successfully be simulated as materials with soil geotechnical behavior.